2016
DOI: 10.31018/jans.v8i4.1082
|View full text |Cite
|
Sign up to set email alerts
|

Maximum rainfall probability distributions pattern in Haryana –A case study

Abstract: The present study has been undertaken to fit best probability distribution of rainfall in Ambala District of Haryana State. The analysis showed that the maximum daily rainfall among the years ranged between 41mm (1980) to 307.9mm (2009) indicating a very large variation during the period of study. The mean of maximum daily rainfall of all years annually is 112.13mm. The means of monthly and weekly values ranged from 33.10-88.92mm and 8.77- 46.28 mm, respectively. The maximum daily rainfall in a year/monsoon se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Coronado-Hernández et al [26] reported GEV as the best fit probability distribution for frequency analysis of maximum daily rainfall for a series of return periods for selected precipitation recording stations in Colombia and also reported GEV to be the best fit for most of the rain-gauge stations considered in Bangladesh. Likewise, Kumar et al [27] gave credence to GEV as the best-performed distribution for most of the rainfall period considered for Haryana, India. Furthermore, Młyński et al [12] recommended GEV distribution to predict maximum daily rainfall with the specific probability of exceedance for catchments in the upper Vistula basin of Poland.…”
Section: Resultsmentioning
confidence: 91%
“…Coronado-Hernández et al [26] reported GEV as the best fit probability distribution for frequency analysis of maximum daily rainfall for a series of return periods for selected precipitation recording stations in Colombia and also reported GEV to be the best fit for most of the rain-gauge stations considered in Bangladesh. Likewise, Kumar et al [27] gave credence to GEV as the best-performed distribution for most of the rainfall period considered for Haryana, India. Furthermore, Młyński et al [12] recommended GEV distribution to predict maximum daily rainfall with the specific probability of exceedance for catchments in the upper Vistula basin of Poland.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, Młyński et al (2019) identi ed GEV as suitable for estimating maximum daily rainfall and probability of exceedance in the Upper Vistula Basin of southern Poland. Kumar et al (2016) tted maximum weekly, monthly, seasonal and annual 47 years rainfall data to different probability distributions and found GEV as the best distribution for most periods considered for Ambala district of Haryana State, India. Beskow et al (2015) found out that rainfall modelled in extreme southern Brazil gives the best result when modelled with multi-parameter probability distributions, of which the kappa multi-parameter distribution had better performance than GEV from this study.…”
Section: Introductionmentioning
confidence: 99%